2014
DOI: 10.1179/1743284714y.0000000598
|View full text |Cite
|
Sign up to set email alerts
|

NiTiHf-based shape memory alloys

Abstract: NiTiHf-based shape memory alloys have been receiving considerable attention for high temperature, high strength and two-way shape memory applications since they could have transformation temperatures above 100°C, shape memory effect under high stress (above 500 MPa) and superelasticity above 100°C. Moreover, their shape memory properties can be tailored by microstructural engineering. However, NiTiHf-based alloys have some drawbacks such as low ductility and high slope in stress induced martensite transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(57 citation statements)
references
References 74 publications
1
47
0
5
Order By: Relevance
“…8b. Their ability to show superelasticity at temperatures near or above 100°C makes them promising high-temperature shape memory alloys and alternatives to NiTiHf alloys [29,33]. Thermal experiments revealed that transformation temperatures are highly dependent on B content in CuAlMnB alloys.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…8b. Their ability to show superelasticity at temperatures near or above 100°C makes them promising high-temperature shape memory alloys and alternatives to NiTiHf alloys [29,33]. Thermal experiments revealed that transformation temperatures are highly dependent on B content in CuAlMnB alloys.…”
Section: Resultsmentioning
confidence: 98%
“…1b. It should be noted that B3 and B4 alloys can be considered as hightemperature shape memory alloys since they have transformation temperatures near or above 100°C [29]. Hardness measurements were taken at room temperature when all the alloys were martensite and were found to increase with the addition of B.…”
Section: Methodsmentioning
confidence: 99%
“…They can operate at high stress levels without the development of significant plastic strains (Karaca et al, 2014). From the analysis of NiTiHf actuator fatigue tests, we see that the number of cycles to failure increases with decreasing cyclic actuation work.…”
Section: Motivating Observations From Previous Studiesmentioning
confidence: 92%
“…), NiTi ve NiTi-bazlı alaşımlar, dayanım, birim şekil değişim miktarı, korozyon dayanımı, tribolojik özellikleri, biyouyumluluk gibi etkileyici özelliklerinden dolayı üzerinde oldukça fazla çalışılan ve diğer alaşım sistemlerinin (NiTiHf, NiTiPd, NiTiCu, NiTiHfPd, NiTiHfCu vb.) üretiminde temel olarak kullanılan alaşımlardır [10][11][12][13][14]. Bundan dolayı, pratik uygulamalarda en çok kullanılan ve kullanılma potansiyeli olan alaşım sistemleri de NiTi ve NiTi-bazlı alaşım sistemleridir.…”
Section: şEkilunclassified